Comparative Study of Traditional and Molecular Methods of Diagnosis and Resistance Determination in Paediatric Pulmonary Tuberculosis Samples - Prachi Singh; Pooja Chaurasia; Ankit Pachauri; Vani Narayani (National Board of Examinations Journal of Medical Sciences)
Background: The burden of childhood tuberculosis provides the measure of tuberculosis control in a community as it reflects recent transmission. The paucibacillary nature of the disease and the inability to produce sufficient volumes of sputum severely hamper accurate diagnosis of tuberculosis in children. It is also equally important to address drug-resistant tuberculosis. Cartridge-Based Nucleic Acid Amplification Test (CBNAAT) is one such test that aids in the rapid detection of Mycobacterium tuberculosis and also rifampicin resistance simultaneously. Very limited studies are available in pediatric cases of pulmonary tuberculosis on the efficacy of CBNAAT compared to other conventional and molecular methods. Material & Methods: 50 children less than 15 years of age suspected to have pulmonary tuberculosis according to National TB Guidelines 2012 were included in the study. Pulmonary samples such as sputum samples (n = 30) and gastric aspirates (n = 20) were collected and sent for testing. Results: Among the 50 subjects, 78% were Tuberculin skin test (TST) positive, 14% were positive for AFB microscopy, CBNAAT was positive in 80%, liquid culture was positive in 40%, and PCR was positive in 52%. Using CBNAAT, n = 34 patients were rifampicin sensitive, and n = 6 were rifampicin resistant. Conventional DST (n = 20) showed RR pattern (resistance to both INH and Rifampicin) in n = 3 and SS pattern (sensitivity to both INH and Rifampicin) in n = 17. LPA (n = 22) showed RR pattern in n = 3, SR pattern (INH sensitive/Rifampicin resistance) in n = 1, and SS pattern in n = 18. Conclusion: CBNAAT results are quite promising for the diagnosis of pulmonary TB in paediatric patients residing in highly TB-endemic countries compared to other tests. It is the least time-consuming test and has the extra benefit of simultaneous Rifampicin resistance detection, which will be a great aid for treatment planning.